Pilar-pilar Manajemen Mutu Terpadu di Pondok Pesantren as-Sunnah Bagiknyaka - Sawaliyah, Yuniarsih; Azhar, Azhar (Asian Journal of Islamic Studies and Da'wah, 2024)
The background to this study is an issue that is often reported in various mass media, regarding the interest of people who choose to send their children to Boarding School. One of the Islamic boarding schools in Indonesia is the As-Sunnah Bagiknyaka Islamic Boarding School. This type of research is a program evaluation with a descriptive-quantitative design used to evaluate the Integrated Quality Management program. The evaluation model used is the discrepancy evaluation model. The conclusions of this research are: The level of effectiveness of the customer focus quality pillar; total involvement; measurement; commitment; and the quality pillar of continuous improvement is included in the effective category. The average satisfaction level for each aspect based on assessments from high school and middle school students, religious teachers, and the results of high school and middle school documents was 74.3%; 73.9%; 67.3%; 74.3%; and 70.4%. Referring to the satisfaction criteria set, this figure falls into the range of 61%-80% which is classified as satisfied, meaning that the level of effectiveness in the five quality pillars at the As-Sunnah Bagiknyaka Islamic Boarding School is in the effective category.